Analisis Penurunan Motivasi Belajar Mahasiswa dan Faktor-faktor yang Mempengaruhinya di Masa Pandemi Covid-19 - Wahyuningsih, Baiq Yuni (YASIN, 2022)
This study aims to analyze students' learning motivation in mathematics during the Covid-19 pandemic. The COVID-19 pandemic is a health crisis that occurs throughout the country and has an impact on many sectors and one of them is the education sector. Therefore, to reduce the spread of the corona virus, the government asks all students from the Kindergarten to Higher Education levels to do online learning from home. This study uses a qualitative method with a descriptive type of research which is intended to create a description of student learning motivation during online lectures during the covid-19 pandemic. Purposive Sampling method was used in determining research subjects and data collection techniques were carried out by questionnaires (via google form), interviews and documentation. Based on 7 indicators assessed including concentration, curiosity, enthusiasm, independence, readiness, enthusiasm and self-confidence, in general the results show students' motivation to learn during the Covid-19 pandemic, found results of 58.16% which are included in the enough category.